Answer:
{x,y} = {3,1}
Explanation:
// Solve equation [1] for the variable x
[1] x = -2y + 5
// Plug this in for variable x in equation [2]
[2] 3•(-2y+5) + 5y = 14
[2] - y = -1
// Solve equation [2] for the variable y
[2] y = 1
// By now we know this much :
x = -2y+5
y = 1
// Use the y value to solve for x
x = -2(1)+5 = 3
Solution :
For this case we have the following system of equations:
To solve, we multiply the first equation by -3:
We add the equations:
We look for the value of the variable "x":
Thus, the solution of the system is (3,1)
(3,1)
5.7m questions
7.5m answers